Blaschke products of given quantity index for a half-plane - Mikayelyan, Gagik; Hayrapetyan, Feliks (Armenian Journal of Mathematics, 2022)
We investigate the growth of the integral logarithmic means of Blaschke products for the half-plane. We prove the existence of Blaschke products of given quantity indices.
Keywords: Blaschke Product; Integral Mean; Quantity Index